2002
DOI: 10.4141/s01-072
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of heavy metals in soils amended with sewage sludge

Abstract: Morera, M. T., Echeverría J. and Garrido, J. 2002. Bioavailability of heavy metals in soils amended with sewage sludge. Can. J. Soil Sci. 82: [433][434][435][436][437][438]. The recycling of sewage sludge to agricultural land results in the slow accumulation of potentially toxic heavy metals in soils. A greenhouse experiment was conducted to determine the bioavailability of Cu, Ni, Pb and Zn applied to soils in urban anaerobically stabilized sewage sludge. The soils were Lithic Haplumbrept (Lh), Calcixerollic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 22 publications
2
40
3
1
Order By: Relevance
“…It has been shown that crop production is favored by the land application of SS (Antolín et al, 2005;Singh & Agrawal, 2008). Morera et al (2002) reported that sludge amendment at the rate of 80, 160 and 320 t/ha DW in soil increased the average dry weight of sunflower plantlets (Helianthus annuus L.). Sludge amendment (SSA) (30,45,60,90 and 120 t/ha) enhanced stomatal conductance and photosynthetic rate of rice (Oryza sativa L.) (Singh & Agrawal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that crop production is favored by the land application of SS (Antolín et al, 2005;Singh & Agrawal, 2008). Morera et al (2002) reported that sludge amendment at the rate of 80, 160 and 320 t/ha DW in soil increased the average dry weight of sunflower plantlets (Helianthus annuus L.). Sludge amendment (SSA) (30,45,60,90 and 120 t/ha) enhanced stomatal conductance and photosynthetic rate of rice (Oryza sativa L.) (Singh & Agrawal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biosolid application has been shown to increase plant biomass in sunflower (Morera et al 2002), maize, barley (Hernandez et al 1991), and cotton (Tsakou et al 2001) and decrease in plant biomass in spinach (Singh and Agrawal 2007) and lettuce (Moreno et al 1997). Logan et al (Logan et al 1997) observed a plateau-type response in the accumulation of Cd, Cu, and Zn concentrations in corn and a linear response in lettuce plants.…”
mentioning
confidence: 99%
“…The ratio of Cd content increase is higher than those for Pb, Cu and Zn [41][42][43]. Wang and co-worker indicated that the addition of 40 t of sewage sludge per ha in rice production resulted in the build-up of about 4, 5, 2, and 11 times more of Cd, Cr, Ni and Pb, respectively, in comparison with non-treated soil.…”
Section: Sewage Sludge Characterizationmentioning
confidence: 99%
“…Zn uptake is greater in the acidic soil than in the alkaline one. The bioavailability of Cu is higher in alkaline soil [41]. Organic matter of sewage sludge is a good adsorptive medium for trace metals in the soil.…”
Section: Sewage Sludge Characterizationmentioning
confidence: 99%